2009
DOI: 10.1007/s10461-009-9602-6
|View full text |Cite
|
Sign up to set email alerts
|

Biological Validation of Self-Reported Condom Use Among Sex Workers in Guinea

Abstract: Self-reported condom use may be prone to social desirability bias. Our aim was to assess the validity of self-reported condom use in a population of female sex workers using prostate specific antigen (PSA) as a gold standard biomarker of recent unprotected vaginal intercourse. We collected data on 223 sex-workers in Conakry, Guinea in order to assess the sensitivity and specificity of self-reported condom use as well as to examine the predictors of discordance between self-report and PSA presence. PSA was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 21 publications
6
41
1
1
Order By: Relevance
“…Reliable, valid, self-reported measurement of condom use is difficult: individuals may not remember whether, how often, and with whom they used condoms over a given time period; they may deliberately misreport due to embarrassment or social desirability bias [67]; or they may unintentionally misreport (e.g., if they experience an unrecognized condom failure). Adjustment for a poorlymeasured confounding variable can in theory lead to adjusted estimates of effect which are more biased than the unadjusted estimates [68].…”
Section: Considerations On Measurement and Parameterization Of Condommentioning
confidence: 99%
“…Reliable, valid, self-reported measurement of condom use is difficult: individuals may not remember whether, how often, and with whom they used condoms over a given time period; they may deliberately misreport due to embarrassment or social desirability bias [67]; or they may unintentionally misreport (e.g., if they experience an unrecognized condom failure). Adjustment for a poorlymeasured confounding variable can in theory lead to adjusted estimates of effect which are more biased than the unadjusted estimates [68].…”
Section: Considerations On Measurement and Parameterization Of Condommentioning
confidence: 99%
“…While the reasons for misreporting in surveys are well-known (e.g., social desirability bias, recall bias), efforts to identify who is more likely to have discrepancies between self-reported survey data and biomarkers, including PSA, have had little success [12,[19][20][21]. In this study, we found that for several women in Group C (concordant), partner influences played a dominant role in their account of why they had unprotected sex, unlike women in Groups A and B (discordant).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies also show that PSA degrades rapidly in the vagina, returning to baseline levels in 24-48 h after exposure [18]. Studies comparing PSA test results with self-reported sexual behaviors have identified high levels of discordance between the two, confirming concerns about the under-reporting of unprotected sexual activity and over-reporting of condom use [7,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Demonstrating an association between biomarkers of semen exposure and STI risk would be useful, given limitations of self-report of sensitive sexual behaviours 5 8–17. Semen biomarkers have been recently used in reproductive health studies to objectively assess recent vaginal semen exposure,6–16 the efficacy of barrier methods of contraception,11 18 19 self-reported condom use14 15 20 21 and study protocol compliance (when it requires avoidance of unprotected sex) 8 21 22. Both Y chromosome–DNA and prostate-specific antigen (PSA) are biomarkers of semen exposure,6 7 11 19 23 with PSA more widely studied and readily available for use in low-resource settings 8–10 19–21 24.…”
Section: Introductionmentioning
confidence: 99%